2017
DOI: 10.1002/eji.201646769
|View full text |Cite
|
Sign up to set email alerts
|

IL4‐induced gene 1 is secreted at the immune synapse and modulates TCR activation independently of its enzymatic activity

Abstract: Amino-acid catabolizing enzymes produced by mononuclear phagocytes play a central role in regulating the immune response. The mammalian phenylalanine-catabolizing enzyme IL4-induced gene 1 (IL4I1) inhibits effector T lymphocyte proliferation and facilitates regulatory T-cell development. IL4I1 expression by macrophages of various human tumors may affect patient prognosis as it facilitates tumor escape from the T-cell response in murine models. Its enzymatic activity appears to participate in its effects, but s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…These observations suggest that IL4I1 can affect both the proliferation and function of this subset. This is supported by several of our previous results: (i) IL4I1 inhibits in vitro human T-cell proliferation by down-regulating TCR signaling (Aubatin et al, 2017;Boulland et al, 2007), (ii) the in vivo escape of B16 melanoma overexpressing IL4I1 is accompanied by reduced expansion of cytotoxic anti-tumor CD8 þ T cells (Lasoudris et al, 2011), and (iii) genetic inactivation of IL4I1 in the mouse Ret model of spontaneous melanoma leads to an increased infiltration of cytotoxic CD8 þ T cells in primary tumors (Bod et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These observations suggest that IL4I1 can affect both the proliferation and function of this subset. This is supported by several of our previous results: (i) IL4I1 inhibits in vitro human T-cell proliferation by down-regulating TCR signaling (Aubatin et al, 2017;Boulland et al, 2007), (ii) the in vivo escape of B16 melanoma overexpressing IL4I1 is accompanied by reduced expansion of cytotoxic anti-tumor CD8 þ T cells (Lasoudris et al, 2011), and (iii) genetic inactivation of IL4I1 in the mouse Ret model of spontaneous melanoma leads to an increased infiltration of cytotoxic CD8 þ T cells in primary tumors (Bod et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…IL4I1 is a secreted L-amino acid oxidase that mainly catabolizes L-phenylalanine to produce hydrogen peroxide, ammonia, and phenylpyruvate. In the past 10 years, IL4I1 has been shown to be expressed by tumor-associated macrophages (TAMs) of numerous cancer types and to regulate T-cell properties both in vitro and in vivo (Aubatin et al, 2017;Boulland et al, 2007;Cousin et al, 2015;Lasoudris et al, 2011;Santarlasci et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated other mechanisms of alternative activation of macrophages. For example, interleukin-4-indiced gene 1 (IL-4I1) has been defined as a strong modulator of alternative macrophage activation (Yue et al, 2015), and is also expressed on DCs (Aubatin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our group has shown that mouse and human IL4I1 are glycosylated and secreted LAAOs that preferentially degrade phenylalanine and, to a lesser extent, arginine [ 11 , 16 ]. IL4I1 limits T lymphocyte activation and proliferation [ 16 , 58 ], in part via the production of H 2 O 2 ( Figure 2 ). A recent interaction of IL4I1 with T lymphocytes has been shown, which could participate in its inhibitory functions, either by concentrating the enzyme at the T cell surface or by mediating a negative intracellular signal [ 58 ].…”
Section: Il4i1 An Laao Implicated In Immune Regulationmentioning
confidence: 99%
“…IL4I1 limits T lymphocyte activation and proliferation [ 16 , 58 ], in part via the production of H 2 O 2 ( Figure 2 ). A recent interaction of IL4I1 with T lymphocytes has been shown, which could participate in its inhibitory functions, either by concentrating the enzyme at the T cell surface or by mediating a negative intracellular signal [ 58 ].…”
Section: Il4i1 An Laao Implicated In Immune Regulationmentioning
confidence: 99%